Self-assembled nanomaterials: design principles, the nanostructural effect, and their functional mechanisms as antimicrobial or detection agents. Issue 9 (17th June 2019) - Li, Li-Li; An, Hong-Wei; Peng, Bo; Zheng, Rui; Wang, Hao
Abstract : Self-assembled nanomaterials have been endowed with designable biofunctions based on non-covalent interactions forming well-ordered nanostructures. Abstract : Self-assembled nanomaterials have been endowed with designable biofunctions based on non-covalent interactions forming well-ordered nanostructures. With various building blocks, nanostructures with multiple dimensional architectures provide abundant functions for biomedical applications, especially as antimicrobial or detection agents. In this review, we discuss naturally sourced assembled nanomaterials and hybrid artificial assembled nanomaterials. We highlight recent contributions to developing strategies for the construction of self-assembled nanomaterials applied to bacterial infection therapy and diagnosis. In addition, the design concept, driving forces of assembly, nanostructural effect, bacterial targeting sites, stimuli-responsive factors, and antimicrobial mechanism are also discussed and summarized. In particular, the relationship between the assembled nanostructures and their antimicrobial mechanisms is emphasized. As a frontier field in supramolecular chemistry, in vivo self-assembled nanomaterials with specific stimuli-responsiveness and surprising biofunctions are also included. Finally, we briefly outline our perspectives on how to explore and fabricate fascinating self-assembled nanomaterials and what challenges are facing this field.